The Image of The Enemy : intelligence analysis of adversaries since 1945 - Maddrell, Paul (Washington, DC : Georgetown University Press, 2015)
This work concerns intelligence analysis of adversaries by six countries, the role of intelligence analysis during the Cold War, and its role in other important regional conflicts after 1945. It seeks to use Cold War and contemporary examples to determine how well intelligence has been analyzed and handled by different intelligence services and policymakers. The book reaches conclusions about past cases in intelligence analysis and how best to analyze intelligence and present it to policymakers today. The book also examines how well policymakers have received and understood intelligence. In sum, the volume analyzes how effective intelligence has been in the policymaking process. It will be a leading text on the analyst/policymaker relationship. The historical cases examined are the Soviet Union's analysis of the United States (and vice versa), East Germany's analysis of West Germany (and vice versa), British intelligence on the early years of the "Troubles" in Northern Ireland, Israeli intelligence on the Palestinians, Pakistani intelligence on India, and US intelligence about Islamist terrorists. Introduction : achieving objective, policy-relevant, intelligence / by Paul Maddrell -- Soviet intelligence, soviet leaders, and changing views of the United States, 1965-1991 / by Raymond L. Garthoff -- The Stasi's reporting on the Federal Republic of Germany / by Paul Maddrell -- "We may not always be right, but we're never wrong" : US intelligence assessments of the Soviet Union, 1972-1991 / by Benjamin B. Fischer -- East Germany in the sights of the West German federal intelligence service (BND) : four examples from as many decades / by Matthias Uhl -- British intelligence, PIRA and the early years of the Northern Ireland crisis : remembering, forgetting, and mythologizing / by Eunan O'Halpin -- Israeli intelligence threat perceptions of Palestinian terror organizations, 1948-2008 / by Tamir Libel and Shlomo Shpiro -- Pakistani intelligence and India / by Julian Richards -- American intelligence assessments of the jihadists, 1989-2011 / by Mark Stout -- Conclusion : intelligence and policy / by Paul Maddrell.
Includes bibliographical references and index.
Keywords: Intelligence service -- Case studies